Feature extraction of neural networks applied to magnetic models (2018)
"The weight matrices of a neural network capable of classifying the phases of the square lattice Ising model, were studied in order to identified the physical features that such an algorithm identifies. A review of the theory of neural networks and condensed matter physics is also included."--Tomado del Formato de Documento de Grado